The relationship between hygiene factors and job satisfaction of employees among engineer at the workplace / Nor Amirah Syed Hussin - Syed Hussin, Nor Amirah (Faculty of Business and Management, 2019)
This paper examines that motivates employee in the manufacturing industry, and examines their level of job satisfaction, using Herzberg’s hygiene factors. Job satisfaction explains individuals’ reactions towards their job. Many studies find that job satisfaction is a well-known construct that is widely used to study work-related wellbeing and contributes significantly to employees’ overall quality of life. Moreover, job satisfaction of employee will encourage healthy and happy working environment of employees in an organization. Besides that, job satisfaction is the mental feeling of favorableness which an individual has about his job. It is often said that “A happy employee is a productive employee.” This shows that, job satisfaction is very important because most of the people spend a major portion of their life at their working place. The current paper examines job satisfaction among Malaysian employees using the Job Satisfaction Survey (JSS). This research will be conducted in the Germen Company in Semiconductor and Manufacturing Industry, Malacca and there are 120 engineers as a sample. The questionnaire was prepared and distributed to the target respondent who is engineers. Since there are many positions of engineers in the organization, the questionnaire will distribute for employee who work in four different of position which are from Process engineers, Quality engineers, Software engineers and also Product engineers. This is because different position of engineers has different has own opinion and suggestion regarding the factors of job satisfaction.